Production responses of multiparous dairy cattle with differing prepartum muscle reserves and supplementation of branched-chain volatile fatty acids - K.M. Gouveia; L.M. Beckett; T.M. Casey; J.P. Boerman (Journal of Dairy Science)
ABSTRACT: Periparturient dairy cattle undergo physiological adaptations to support fetal growth and colostrum synthesis in late gestation and milk production in early lactation. To support energy and protein demands, dairy cattle mobilize body tissue reserves. The objective of this study was to determine the effects of prepartum skeletal muscle reserves and supplementation of branched-chain volatile fatty acids (BCVFA) on body composition measurements, metabolic markers related to health, protein, and energy status, and subsequent milk yield in multiparous dairy cows. Skeletal muscle reserves were assessed by 3 ultrasounds of the longissimus dorsi muscle depth (LDD) measured 42 d before expected calving, and cows (n = 48) were assigned to either high muscle (HM; >4.6 cm) or low muscle (LM; ≤4.6 cm) groups. Cows were then randomly assigned to either control (CON) of soyhull pellets (80 g/d) or BCVFA treatment, which contained isobutyrate (40 g/d), isovalerate (20 g/d), and 2-methylbutyrate (20 g/d) calcium salt products. Treatments were top dressed from 42 d before expected calving until parturition, resulting in 4 combinations of muscle groups and treatments: HM-CON (n = 13), HM-BCVFA (n = 13), LM-CON (n = 11), and LM-BCVFA (n = 11). Measurements of the LDD, BW, and BCS were taken on the following days relative to calving: −42, −35, −21, −7, 0, 7, 14, 21, 28. Weekly blood samples were taken to measure glucose, BHB, and insulin concentrations, and 5 of the blood sample time points were used to determine 3-methylhistidine and creatinine blood concentrations. Milk yield was recorded daily for the first 28 d of lactation, and samples were taken from both milkings once a week for the first 4 wk to determine components. The statistical model included the fixed effects of treatment, group, time, and their interactions, and the random effect of cow nested within group and treatment. Prepartum muscle mobilization varied between muscle groups, as LM cows accreted muscle prepartum, and HM cows mobilized muscle. The HM cows had higher milk fat, protein, lactose, and energy-corrected milk yields. The BCVFA supplementation tended to increase blood glucose concentrations both prepartum and postpartum and decreased milk urea nitrogen concentrations. Greater prepartum skeletal muscle reserves improve productivity of early-lactation cows, likely due to differences in muscle mobilization, and BCVFA supplementation improves glucose dynamics during the transition period, which may improve the metabolic health of the periparturient dairy cow.